RIFM fragrance ingredient safety assessment, N-(2-(pyridin-2-yl)ethyl)-3-p-menthanecarboxamide, CAS Registry Number 847565-09-7. (15th April 2020) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Highlights: N-(2-(Pyridin-2-yl)ethyl)-3- p -menthanecarboxamide; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.